Mechanism of Fingerprint Conversion to Text - Yahya Ali, Nashwan; Thakare, VM (International Journal of Computer Sciences and Engineering, 2025)
One of the important methods of identifying a person is fingerprint because it has several features like invariability, uniqueness and more. Nowadays, many databases hold fingerprint columns and these columns may be search based columns. Database may incur overload search on fingerprint columns which represent a bottleneck to the system. We proposed a method that convert the fingerprint to text which improves the performance of the system and many more other benefits. Fingerprint image is converted to text which is smaller in size that helps in processing as well as storage space. Smaller size of data also is better in transmission over network. In the term of data encryption, text encryption is easier and has less time complexity than of images.